Phylogenetic Variation in the Silicon Composition of Plants - HODSON, M. J. (Ann Bot, 2005)
• Background and Aims Silicon (Si) in plants provides structural support and improves tolerance to diseases, drought and metal toxicity. Shoot Si concentrations are generally considered to be greater in monocotyledonous than in non-monocot plant species. The phylogenetic variation in the shoot Si concentration of plants reported in the primary literature has been quantified. • Methods Studies were identified which reported Si concentrations in leaf or non-woody shoot tissues from at least two plant species growing in the same environment. Each study contained at least one species in common with another study. • Key Results Meta-analysis of the data revealed that, in general, ferns, gymnosperms and angiosperms accumulated less Si in their shoots than non-vascular plant species and horsetails. Within angiosperms and ferns, differences in shoot Si concentration between species grouped by their higher-level phylogenetic position were identified. Within the angiosperms, species from the commelinoid monocot orders Poales and Arecales accumulated substantially more Si in their shoots than species from other monocot clades. • Conclusions A high shoot Si concentration is not a general feature of monocot species. Information on the phylogenetic variation in shoot Si concentration may provide useful palaeoecological and archaeological information, and inform studies of the biogeochemical cycling of Si and those of the molecular genetics of Si uptake and transport in plants.